The The Influence Of Environment And Family Communication Patterns On The Occurrence Of Speech Delay In Children In Gampong Lambaroangan, Darussalam District, Aceh Besar Regency: Environment, Communication Patterns, Family, Child Speech Delay - Mela Hayani; Muhammad Reza Rizki; Reca Melati Phonna (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
The family environment is very influential on the development of children's speech. Early childhood speech delay requires special treatment and more attention from families, especially parents, in order to improve children's language development, so that children are able to communicate well in the family and community environment. The existence of interaction activities between family members, especially for children aged 3-5 years through communication patterns and stimuli, will determine the basis for providing speaking skills to children. This study uses quantitative with purposive sampling method, namely sampling with certain criteria or considerations. Where researchers want to know the relationship between the variables studied, namely The influence of the environment and family communication patterns on the occurrence of speech delay in children in Gampong Lambaroangan, Darussalam District, Aceh Besar Regency. The population of this study were children who experienced speech delay with a sample of 60 people obtained from observations through Puskesmas and Posyandu activities. Through this sample, 72.1% of fathers were found to be early adults with 61.0% secondary education level and had 32.0% occupation as traders, while 82.2% of mothers were early adults with 64.7% secondary education level and only 40.3% as housewives. Also through the results of the study obtained a significance value smaller than 0.05 (0.000 <0.05) and a correlation coefficient value of 0.632. Based on the results of the data obtained from the analysis conducted, it can be concluded that there is a significant influence between the environment and family communication patterns on the occurrence of speech delay in children in Gampong Lambaroangan, Darussalam District, Aceh Besar Regency.